Neutral hydrogen mass distributions in galaxies uncovered by three-dimensional stacking - Firth, Andrew (Department of Astronomy, 2025)
Atomic hydrogen (HI) serves as the raw fuel from which the star-forming molecular hydrogen forms - making it an important tracer of galaxy evolution. Due to the intrinsic faintness of the HI emission line (observed at rest at 21 cm), detecting HI emission in galaxies beyond a z = 0.1 becomes difficult, thus, many statistical techniques have since been developed in order to extend the capabilities of already rapidly improving radio observatories. HI stacking is one such technique, involving the co-addition of the HI spectra of a sample of galaxies, exploiting statistical properties of random noise to achieve a high signal-to-noise measure of their average HI content. While this technique focuses on extracted one-dimensional spectra, research extending this concept to the parent data-cube of the one-dimensional spectra is a growing area of research. Studies such as those by (Chen et al., 2021; Sinigaglia et al.,2022) focus on stacking in three-dimensions to improve the point-spread function, HI signal detectability, and hence improve HI mass measurements.We present an initial exploration of a novel approach to stacking, working at the level of imaged radio cubelets, i.e., in three dimensions (3D). Unlike previous stacking works focusing on the UV-plane, and extracts a one-dimensional profile to recover the average HI-mass of the stack, we attempt to recover fine structure within the stack. While our sample sizes prove to be the reason for the limited results, we demonstrate the potential increase in signal-to- noise by assessing the effect sigma-clipping a of stacking on galaxy surface-brightness profiles; comparing one-dimensional and three-dimensionally co-added techniques simultaneously. Using full-resolution data cubes from the Noordermeer et al. (2005) sub-sample of Wester- bork observations of neutral Hydrogen in Irregular and Spiral galaxies (WHISP) survey (van dermHulst et al., 2001), we make use of the homogeneous data reduction pipeline, well-documented global properties, and mass-distribution studies to calibrate our stacking suite. In developing this pipeline, we demonstrate the concept of aligning signal through various geometric transformations (rotation, stretching, and spectral-inversion) as a first approach to a ‘Comprehensive Unearthing of Baryons in Extended-regions using a Stacker' (Cube Stacker). Developed in Python 3.8, this pipeline bridges the gap of stacking techniques targeted at re-solved targets, preserving structure with the aim of utilising an improved SNR to uncover faint HI features. While our stacking is based on 21cm measurements of HI distributions, we ex-plore the possibility of utilising galaxy scaling-relations - incorporating the high-fidelity optical measurements of galaxies to be observed with high-sensitivty facilities such as MeerKAT. Thus, we present measures of central concentration (i.e. C80,20) for the 33 NSA-selected galaxies, and discuss the merits of an optically-based stacking-pipeline in uncovering faint HI in existing or upcoming blind surveys.